Sticky situations: 'Force' and quantifier domains - Mandelkern, M; Phillips, J (Linguistic Society of America, 2018)
When do we judge that someone was forced to do what they did? One relatively well-established finding is that subjects tend to judge that agents were not forced to do actions when those actions violate norms. A surprising discovery of Young and Phillips 2011 is that this effect seems to disappear when we frame the relevant ‘force’-claim in the active rather than passive voice ('X forced Y to φ' vs. 'Y was forced to φ by X'). Young and Phillips found a similar contrast when the scenario itself shifts attention from Y (the forcee) to X (the forcer). We propose that these effects can be (at least partly) explained by way of the role of attention in the setting of quantifier domains which in turn play a role in the evaluation of ‘force’- claims. We argue for this hypothesis by way of an experiment which shows that sequences of active vs. passive ‘force’-claims display the characteristic “stickiness” of quantifier domain expansion, using a paradigm which we argue provides a useful general paradigm for testing quantifier domain hypotheses. Finally, we sketch a semantics for ‘force’ which we argue is suitable for capturing these effects.